Synthesis and In vitro evaluation of bichalcones as novel anti-toxoplasma agents - Mazzone, Flaminia; Klischan, Moritz K. T.; Greb, Julian; Smits, Sander H. J.; Pietruszka, Jörg; Pfeffer, Klaus (Frontiers in Chemistry, 2024)
Toxoplasmosis is a zoonotic disease caused by Toxoplasma gondii, an apicomplexan parasite that infects approximately a third of the world's human population. This disease can cause serious complications during pregnancy and can be fatal in immunocompromised hosts. The current treatment options for toxoplasmosis face several limitations. Thus, to address the urgent medical need for the discovery of novel anti-toxoplasma potential drug candidates, our research focused on exploring a series of monomeric and dimeric chalcones, polyphenolic molecules belonging to the class of flavonoids. Chalcones 1aa -1bg and axially chiral A-A'-connected bichalcones 2aa -2bg were evaluated in vitro against the proliferation of the parasite in a cell-based assay. A comparison of the efficacy demonstrated that, in several cases, bichalcones exhibited increased bioactivity compared to their corresponding monomeric counterparts. Among these compounds, a bichalcone with a phenyl substituent and a methyl moiety 2ab showed the most potent and selective inhibitory activity in the nanomolar range. Both enantiomers of this bichalcone were synthesized using an axially chiral biphenol building block. The biaryl bond was forged using Suzuki cross-coupling in water under micellar catalysis conditions. Separation of the atropisomers of this biphenol building block was conducted by chiral HPLC on a preparative scale. The biological evaluation of the enantiomers revealed that the (Ra)-enantiomer (Ra)-2ab is the eutomer. These studies suggest that bichalcones may be important drug candidates for further in vivo evaluations for the discovery of anti-toxoplasma drugs.